Pendampingan kepada Masyarakat untuk Meningkatkan Program Sadar Wisata di Kelurahan Tlogopatut, Kabupaten Gresik - Kurniawan, Syahrul Dwi; Ikaningtyas, Maharani Ikaningtyas (Jurnal Bisnis Indonesia, 2024)
This community service aims to encourage tourism awareness in Tlogopatut Village. Through theimplementation of a tourism awareness program, we seek to mobilize community participation in thepreservation and development of local tourist destinations. The community service method includestraining, workshops, and promotion to increase tourism awareness. The result is a significant increasein tourism awareness in this kelurahan, which is reflected in the active participation of the communityin tourism-related activities. Positive impacts were also seen in the development of local tourismdestinations. However, challenges in the implementation of this program remain, such as coordinationbetween various related parties and sustainable planning. The results of this service provide positiveimplications for the development of sustainable tourism in the village and can serve as a guide forother villages in encouraging tourism awareness.Keywords: Tourism; Mentoring; Destinations Program; Community Awereness